2019
DOI: 10.1111/and.13464
|View full text |Cite
|
Sign up to set email alerts
|

The changes in semen quality, arginase activity and nitric oxide level in dexamethasone‐treated rams

Abstract: This study was made to investigate the effects of intramuscular administrations of dexamethasone on seminal plasma nitric oxide levels and arginase activity, and some spermatological parameters in rams. Ten Akkaraman rams weighing 50–60 kg and 2 years old were used as material in this study. The study was performed during the breeding season (September–November) for rams. The semen was collected by artificial vagina at 1st, 4th, 24th, 48th, 72nd and 96th hours for control group before dexamethasone administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…In the present study sGC‐exposure did not influence sperm motility, morphology, vitality or count in either the caput or cauda sections of the epididymis and did not influence plasma testosterone concentrations. This is in contrast to previous studies that demonstrate significant reductions to sperm parameters in other species 9,12 . For instance, a study in rams demonstrated that two intramuscular Dex (0.25 mg/kg) injections resulted in decreases in sperm motility, sperm density, semen volume, and increased abnormal sperm rate 9 .…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…In the present study sGC‐exposure did not influence sperm motility, morphology, vitality or count in either the caput or cauda sections of the epididymis and did not influence plasma testosterone concentrations. This is in contrast to previous studies that demonstrate significant reductions to sperm parameters in other species 9,12 . For instance, a study in rams demonstrated that two intramuscular Dex (0.25 mg/kg) injections resulted in decreases in sperm motility, sperm density, semen volume, and increased abnormal sperm rate 9 .…”
Section: Discussioncontrasting
confidence: 89%
“…This is in contrast to previous studies that demonstrate significant reductions to sperm parameters in other species. 9,12 For instance, a study in rams demonstrated that two intramuscular Dex (0.25 mg/kg) injections resulted in decreases in sperm motility, sperm density, semen volume, and increased abnormal sperm rate. 9 Similarly, a study in mice found that seven day intraperitoneal injection of Dex (7 mg/kg/day) significantly decreased sperm motility, the number of spermatocytes, spermatogenesis index and serum testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semen arginase activity is related to sperm count and motility in humans (Elgün, Kaçmaz, Sen, & Durak, 2000), rams (Gür & Kandemir, 2012) and goats (Türk, Gür, Kandemir, & Sӧnmez, 2011;Daramola & Adekunle, 2017). Oxidative perturbations exhibited by administration of dexamethasone in ram caused a decreased arginase activity in ram semen (Kaya et al, 2020). In fact, arginase activity in seminal plasma of mammalian males could be used as a biochemical criterion to indicate the quality of semen.…”
Section: Discussionmentioning
confidence: 99%